Cashless Lifestyle among Generation Z: Implications for Islamic Banking Digital Transformation in Medan City - Chindy Jihan Najiyah; Kusmilawaty; Muhammad Lathief Ilhamy Nasution (Jurnal Investasi Islam, 2026)
The rapid growth of digital payment systems has accelerated the emergence of a cashless society, particularly among Generation Z. Although previous studies have examined the determinants of cashless payment adoption, limited research has explored how cashless behavior influences lifestyle changes and its implications for Islamic banking digital transformation. This study aims to analyze Generation Z’s cashless payment behavior and its implications for Islamic banking in Medan, Indonesia. The Technology Acceptance Model (TAM) serves as the analytical framework, focusing on perceived usefulness and perceived ease of use. A qualitative exploratory approach was employed through semi-structured interviews and observations involving four Generation Z participants. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that perceived usefulness and perceived ease of use are the primary drivers of cashless payment adoption. Cashless usage has reshaped Generation Z’s lifestyle through increased transaction intensity, greater consumption flexibility, and more technology-oriented financial management. However, the study reveals that high adoption of digital payments does not automatically lead to greater adoption of Islamic banking services. Instead, service quality, system reliability, and user experience are more influential factors. This study contributes to the literature by linking TAM, cashless behavior, lifestyle change, and Islamic banking digital transformation within the context of the digital economy.